Rancang Bangun Sistem Informasi Manufaktur "Sepatu Bordir.ID Malang" Menggunakan Metode Rapid Application Development Modul: Produksi, Logistik dan Pembelian - Cut Naurah Cassrisa; Nurudin Santoso; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
SepatuBordir.ID business is a shoe made in a country located in Malang, in SepatuBordir.ID business in Malang has several processes in making shoes, ranging from raw materials to shoes or finished goods. In the process of making shoes, several actors are involved, namely production, logistics, and purchasing to support shoe making because there is a process to manage production data that functions to plan all uses of raw materials to be processed. Logistics that serves to process all raw materials, both incoming materials or materials that will be issued in the process of making shoes. The condition experienced in the SepatuBordir.ID business is that all data processed is still using manual or non-computer methods that are still recorded in books. Therefore, the problem obtained is finally used as a background for designing systems that are useful for processing data on production, logistics and purchasing. So from the information that has been obtained, the technology is implemented in a web form that focuses on the field of manufacture related to the process of making embroidery shoes. To produce a useful website for SepatuBordir.ID, a needs analysis is carried out which produces 12 functional requirements for the production department, 18 functional requirements for the logistics department, then there are 9 functional requirements that exist in the purchase then the system developed chooses additional requirements namely non-functioning. This study uses the Rapid Application Development method, with the white box testing method aimed at the system unit and black box testing aimed at the functional system. then the usability testing will be done which is useful to find out whether the system can be used by customers without direction from the developer